Faith, Knowledge, and Charity: Communication and Implementation in University Life / Iman, Ilmu, dan Amal: Komunikasi dan Implementasinya dalam Kehidupan Universitas - Nurhadi, Zikri Fachrul; Ranita, Dian; Salamah, Ummu (UIN Antasari Banjarmasin, 2024)
This research is motivated by the results of a survey on the understanding of the motto